The Seed Of Sally Good'n : A Black Family of Arkansas, 1833-1953 - Patterson, Ruth Polk, 1930- (Book collections on Project MUSE., 1985)
Robert Polk came to America from Donegal, Ireland and settled on the eastern shores of Maryland. From here, his descendants scattered over the new colonies from Cumberland County, Pennsylvania to Mecklenberg County, North Carolina. Here Taylor Polk was born in 1780. He was the fourth generation of Polks born in America. The Polks moved to Tennessee and eventually to what would become Arkansas.